2017
DOI: 10.1001/jamapediatrics.2016.2681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Increased Enteral Protein Intake on Growth in Human Milk–Fed Preterm Infants

Abstract: IMPORTANCE Protein, supplied in currently available commercial fortifiers, may be inadequate to meet the requirements of very preterm infants; in addition, intraindividual and interindividual variability of human milk protein and energy content potentially contribute to unsatisfactory early postnatal growth. OBJECTIVE To determine effects on growth of different levels of enteral protein supplementation in predominantly human milk-fed preterm infants. DESIGN, SETTING, AND PARTICIPANTS This randomized clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 18 publications
6
40
1
Order By: Relevance
“…Regarding the effects of the fortification protocol on growth, we did not find any significant difference between the two groups up to the 12th month CA. Our findings are in agreement with previous studies in preterm infants fed fortified human milk with variable protein content [49][50][51]. However, a higher rate of weight gain in preterm infants receiving increased amounts of protein was reported by other authors [25,[52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding the effects of the fortification protocol on growth, we did not find any significant difference between the two groups up to the 12th month CA. Our findings are in agreement with previous studies in preterm infants fed fortified human milk with variable protein content [49][50][51]. However, a higher rate of weight gain in preterm infants receiving increased amounts of protein was reported by other authors [25,[52][53][54][55][56].…”
Section: Discussionsupporting
confidence: 94%
“…Specifically, in most studies, a proportion or all included infants were fed exclusively or partly banked donor milk [50][51][52][53][54][55], which contains lower protein than the preterm OMM [4,65], thereby requiring a higher fortification level. In other studies, a protein content of about 0.8-1.4 g/dL in human milk was assumed [49][50][51]54] or the protein intake was adjusted to blood urea levels [50,51,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Results of several randomised controlled trials suggest that the gap cannot be overcome by increasing the amounts of amino acids provided by parenteral nutrition [28-30], whereas adding protein to human milk promotes the growth of extremely preterm infants [31-34]. However, there is an apparent ceiling at around 4 g/kg/day [35]. …”
Section: Discussionmentioning
confidence: 99%
“…A 2017 RCT of 60 preterm infants by Maas et al. showed that an increase in protein intake by 0.6 g/kg/day to a mean intake of 4.3 g/kg/day throughout the duration of NICU hospitalisation did not improve growth of preterm infants when compared to standard fortification guidelines. Similarly, a separate RCT of 60 preterm infants published in 2018 showed that fortification of human milk with an additional 0.7 g/kg/day of protein did not improve weight, length or head circumference growth during a 4‐week period .…”
Section: Discussionmentioning
confidence: 99%